Digestibility, Growth Performance, Body Measurement and Hormone of Sheep Fed with Different Levels of Brachiaria decumbens Diets - Mimi Syazwani Jaapar; Eric Lim Teik Chung; Nazri Nayan; Kalai Vaani Muniandy; Muhammad Hazziq Mohd Hamdan; Shokri Jusoh; Faez Firdaus Abdullah Jesse (Tropical Life Sciences Research, 2023)
Limited data are available regarding the effects of Brachiaria decumbens on sheep’s growth performance at different times. Therefore, this current study focused on sheep’s nutrient apparent digestibility, feed efficiency, body index, and growth hormone when they are fed with low and high levels of B. decumbens diets. A total of 30 six-month- old male Dorper cross sheep were divided randomly into three treatment groups with 10 sheep per treatment. Treatment 1 (control) sheep were fed with Pennisetum purpureum and pellets as the basal diet, whereas Treatment 2 and 3 sheep were fed with feed mixed with low (10%) and high (60%) levels of B. decumbens, respectively. The study was conducted in two phases consisting of short-term feeding (seven days) and long-term feeding (90 days). Throughout the experiment, daily fecal voided were collected in the morning for seven days continuous before the end of each feeding phases for the determination of nutrient apparent digestibility. The amount of feed offered and refusals plus body weight gain were recorded daily to determine the feed efficiency (FE). Besides, the body measurements of each sheep from every treatment were measured weekly and blood samples were collected for the analysis of growth hormone (GH) concentration. There were significant differences (p < 0.05) in the nutrient apparent digestibility, growth performance, body measurement, and GH concentration among treatment sheep throughout the study period. Treatment 3 sheep fed with 60% of B. decumbens diet revealed the lowest dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF) digestibility during the long-term feeding. Likewise, Treatment 3 (T3) sheep had the lowest total bodyweight gain, average daily gain, total feed intake, and daily feed intake among treatment sheep. The heart girth index (HGI) of T3 sheep was also significantly lower during the short-term feeding. Moreover, the GH concentration of T3 sheep was significantly lower as compared to the control that decreases steadily throughout the study period. In conclusion, high levels of B. decumbens showed the most significant results out of all three treatments indicating the presence of saponins, which produce negative effects on the sheep’s overall performance.